α-Halobenzylzinc halides - Goh, L.Y.; Goh, S.H. (Elsevier, 1970)
ga-Halobenzylzinc halides (C6H5CHXZnX) in tetrahydrofuran decompose via two routes, viz.: insertion into tetrahydrofuran and formation of stilbenes. The stability of C6H5CHXZnX, studied by iodometric titration, was shown to decrease in the order: X = I > Br > Cl. © 1970.